2019
DOI: 10.1038/s41598-019-48701-4
|View full text |Cite
|
Sign up to set email alerts
|

A biomimetic 3D model of hypoxia-driven cancer progression

Abstract: The fate of tumors depends both on the cancer cells’ intrinsic characteristics and on the environmental conditions where the tumors reside and grow. Engineered in vitro models have led to significant advances in cancer research, allowing the investigation of cells in physiological environments and the study of disease mechanisms and processes with enhanced relevance. Here we present a biomimetic cancer model based on a collagen matrix synthesized through a biologically inspired process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 54 publications
4
61
0
Order By: Relevance
“…There are two different types of BC cell lines examined here by the authors: MCF-7 (estrogen-positive BC cells, linked to good prognosis), and MDA-MB-231 (triple negative and aggressive BC cells) [109]. Their discovery shows in this experimental scenario that cells are able to build a hypoxic core niche, with modified growth dynamics, and that more aggressive cancer cells are selected, similarly to what happens during the in vivo disease progression [108].…”
Section: D Scaffold or Hydrogels Based Tumor Modelsmentioning
confidence: 95%
See 1 more Smart Citation
“…There are two different types of BC cell lines examined here by the authors: MCF-7 (estrogen-positive BC cells, linked to good prognosis), and MDA-MB-231 (triple negative and aggressive BC cells) [109]. Their discovery shows in this experimental scenario that cells are able to build a hypoxic core niche, with modified growth dynamics, and that more aggressive cancer cells are selected, similarly to what happens during the in vivo disease progression [108].…”
Section: D Scaffold or Hydrogels Based Tumor Modelsmentioning
confidence: 95%
“…Liverani and colleagues presented a biomimetic 3D tumor model based on macroporous scaffolds, which resembles the hierarchically organized structure of extracellular collagen [107,108]. There are two different types of BC cell lines examined here by the authors: MCF-7 (estrogen-positive BC cells, linked to good prognosis), and MDA-MB-231 (triple negative and aggressive BC cells) [109].…”
Section: D Scaffold or Hydrogels Based Tumor Modelsmentioning
confidence: 99%
“…The authors identified ADAM19 and its epigenetic regulation as a robust new biomarker of EMT in vitro and in vivo (136). With another experimental approach using 3D biomimetic scaffolds, Liverani et al (137) demonstrated that metastatic breast tumors have a higher capability to alter the extracellular collagen structures, affecting the mechanobiology of cell-ECM in metastatic tumors. Moreover, the modification in collagen hydroxylation state was associated with pyruvate metabolism in metastatic breast cancer cell lines (138).…”
Section: Epithelial To Mesenchymal Transition Promotes Extracellular mentioning
confidence: 99%
“…For example, a 3D collagen scaffold model created by Liverani and colleagues (2019), allowed for the culture of breast cancer cells in an environment that mimics the hierarchically organised structure of extracellular collagen in actual tissue. Furthermore, this model permits the study of hypoxia effects on cell fate and metabolism, as tissue-like cellular structures are able to establish realistic oxygen gradients, which contributes to their overall phenotype [ 79 ]. Another invaluable tool in the study of mechanobiology is atomic force microscopy, which permits the mechanical profiling of matrices and individual cells on a nanometre scale.…”
Section: Mechanotransduction In Osteosarcoma and Promising Targetamentioning
confidence: 99%